Prrevious parent Behavior On Parenting Pattens In Elementary School Student In Meuraxa District Banda Aceh - Nur Asiah (Yayasan Darul Hasanah Aceh, 2025)
Previous Parent Behavior On Parenting Patterns In Elementary School Students In Meuraxa District Banda Aceh Maria Ulfa1, Nur Asiah2, Desrina3 1Akademi Keperawatan Teungku Fakinah Banda Aceh, Aceh Indonesia Email: ulfazulkifli27@gmail.com Abstract Parenting is a technique used by parents to educate, protect, and supervise their children in the family. Balanced parenting implementation is very important for the growth and development of children. This study used a descriptive method with a community health nursing approach including the assessment, intervention, implementation, and evaluation. The study on parenting patterns of parents was carried out on an elementary school children aggregate in the Meuraxa Public Health Center area, Banda Aceh using the windshield survey, questionnaires, and interviews with program administrators, parents, teachers, and elementary school students. The assessment was carried out based on Pender's theory (Health Promotion Model/HPM). The study results showed that 104 parents (43.15%) used authoritarian parenting, 137 (56.85%) used democratic parenting, and 0 (100%) used permissive parenting. The results of interviews with parents revealed that parents educate their children following their previous parents’ style, parents never get information on how to raise children according to the proper parenting method, parents were impatient in dealing with children's behavior, parents said that in educating children parents should have adequate knowledge about parenting methods. In this study, the community nursing diagnoses emerged were; the improvement of the public health center management, which can be addressed by providing parenting classes at the Meuraxa Public Health Center. While the intervention for the second community nursing diagnosis; the risk for child abuse was Group-Based Parent Training provided for Maternal and Child Health and School Health Unit program participants. The outcomes of the program evaluation show that participants thought these programs were excellent. It is advised that this study be put into practice to support healthy parenting practices through the use of community nursing care processes. Keywords: Children, Parent Behaviour, Parenting Pattern.